2017
DOI: 10.1097/md.0000000000006508
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus increases the risk of hepatocellular carcinoma in treatment-naïve chronic hepatitis C patients in China

Abstract: We investigated the link between diabetes mellitus (DM) and hepatitis C virus (HCV)-related hepatocellular carcinoma (HCC) risk in treatment-naïve chronic hepatitis C (CHC) patients in China.To examine the association between DM and HCC, we conducted a case–control study of 300 Chinese CHC patients with HCC, compared to an age- and sex-matched control group of 517 CHC patients not diagnosed with HCC.We found that DM was more prevalent in the HCC patient group (18.7%) than in the CHC-only patient group (10.8%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…Many genome-wide association studies (GWAS) have identified many loci that affect the risk of type 2 diabetes [50,51]. There are many hypotheses [52] that explain the association between diabetes and the increased risk of HCC. Diabetes is one of the component of metabolic syndrome that may lead to non-alcoholic steatohepatitis (NASH) and consequently HCC.…”
Section: (G) Diabetesmentioning
confidence: 99%
“…Many genome-wide association studies (GWAS) have identified many loci that affect the risk of type 2 diabetes [50,51]. There are many hypotheses [52] that explain the association between diabetes and the increased risk of HCC. Diabetes is one of the component of metabolic syndrome that may lead to non-alcoholic steatohepatitis (NASH) and consequently HCC.…”
Section: (G) Diabetesmentioning
confidence: 99%
“…4 HCV-associated T2DM has been shown to accelerate the clinical course of chronic HCV infection, significantly increasing the risk of fibrosis and its progression to cirrhosis, decompensation and HCC [15][16][17][18][19][20][21][22][23][24]. Multiple studies have shown a link between T2DM and the development of liver fibrosis.…”
Section: What Is the Clinical Relevance Of T2dm In Patients With Chromentioning
confidence: 99%
“…The concomitant liver disease related to non-viral etiologies accelerates HCV-induced liver disease, cirrhosis development, and HCC. [279][280][281][282][283][284][285][286][287] Obesity is associated with metabolic syndromes such as insulin resistance, type 2 diabetes, and NAFLD. A recent study using more than 900,000 US adults showed that the risk of death related to HCC was 2-fold higher in men with BMI of 30-34.9 and 4.5 times higher with BMI greater than 35.…”
Section: Bystander Oncogenic Mechanisms Overlapping Host-related Non-mentioning
confidence: 99%
“…Diabetes with HCV infection has a 2 to 3-fold increase in HCC risk. [281][282][283][284] The researchers also showed that HCC development increased due to the combined effect of alcohol and chronic HCV infection. [285][286][287] In addition to nonviral agents, co-infection with the hepatitis B virus or human immunodeficiency virus increases the risk of HCC after HCV cure.…”
Section: Bystander Oncogenic Mechanisms Overlapping Host-related Non-mentioning
confidence: 99%